Mental Health Professionals' Experiences with Aphasia. - Morrow-Odom, K. Leigh; Barnes, Chandler K. (Journal of Rehabilitation)
This study used an online survey to examine mental health professionals' awareness of and experiences with persons with aphasia (PWA) and professionals' confidence in treating depression in persons with aphasia. Although the majority of respondents were familiar with aphasia and understood it to be a type of communication disorders, only about half also indicated experience treating persons with aphasia. Further, nearly half reported little or no confidence in providing services to this population. Level of education and years of experience were associated with greater confidence. The results guide future research and training to improve service provision and thus quality of life for persons with aphasia.